1995
DOI: 10.1051/animres:19950535
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment of cottonseed to increase its value as a dairy supplement

Abstract: The objective of this experimentation was to identify the optimum temperature to heat treat cottonseed for the purpose of improving protein utilization, and to measure potential milk production response to feeding of optimally heated cottonseed. Linted cottonseed was roasted to 134, 141, 150, 155, 159, 176

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Milk protein percentage (Table 4) was not affected by ESB supplements compared with diets without ESB and was similar in other researches (Whitlock et al, 2002;Ye et al, 2009). Solomon et al (2000) showed that milk protein content was decreased with the addition of ESB, which would be associated with negative effects on rumen microbial growth observed for cows fed high fat diets (Jenkins, 1993;Satter et al, 1994). The decrease in milk protein content is likely to be consistent with the increased milk urea nitrogen concentrations observed with diets containing ESB and would also be consistent with a dilution of milk protein as milk yield increased (Solomon et al, 2000).…”
Section: Dmi Milk Yield and Milk Compositionsupporting
confidence: 80%
“…Milk protein percentage (Table 4) was not affected by ESB supplements compared with diets without ESB and was similar in other researches (Whitlock et al, 2002;Ye et al, 2009). Solomon et al (2000) showed that milk protein content was decreased with the addition of ESB, which would be associated with negative effects on rumen microbial growth observed for cows fed high fat diets (Jenkins, 1993;Satter et al, 1994). The decrease in milk protein content is likely to be consistent with the increased milk urea nitrogen concentrations observed with diets containing ESB and would also be consistent with a dilution of milk protein as milk yield increased (Solomon et al, 2000).…”
Section: Dmi Milk Yield and Milk Compositionsupporting
confidence: 80%